Functional Recovery Promotion After Spinal Cord Injury With Astaxanthin Treatment in Preclinical Studies: A Systematic Review and Meta-Analysis - Razieh Hajisoltani; Faeze Sadat Ahmadi Tabatabaei; Michael R. Hamblin; Fatemeh Ramezani (Neurology Research International)
Conclusion: Astaxanthin has the potential to be used as an adjuvant in improving motor behavior, and it is suggested to conduct clinical studies on it.